The role of autophagy inhibition in the enhanced cytotoxicity of temozolomide on melanoma cell lines - O. O. Ryabaya; A. N. Inshakov; A. A. Malysheva; I. S. Abramov; N. V. Sholina; D. A. Khochenkov; E. V. Stepanova (Успехи молекулярной онкологии)
Background. Despite advantages in treatment of metastatic melanoma it remains resistant to current therapy. Recent evidence indicates that tumor cells could overcome death through autophagy, a process that degrades cellular proteins and organelles to maintain cellular biosynthesis during nutrient deprivation or lack of energy. Objective: to investigate the involvement of autophagy inhibitors chloroquine (CQ) and LY-294.002 (LY) in temozolomide (TMZ) cytotoxicity in human melanoma cell lines.Materials and methods. The study was performed on patient-derived melanoma cell lines Mel Z, Mel IL and Mel MTP. The antiproliferative activity of combined TMZ and autophagy inhibitors treatment was determined by MTT assay and colony-forming assay. Cell cycle analysis, apoptosis activation and expression analysis of key autophagy markers under combined treatment was evaluated.Results. CQ and LY enhanced the cytotoxicity of TMZ and reduced colony formation in 3 melanoma cell lines, moreover both inhibitors increased cell population in G0 / G1 phase of cell cycle in Mel Z, Mel IL cell lines, but not in Mel MTP. CQ and LY synergistically activated apoptosis in all cell lines. The matrix RNA expression analysis of key autophagy genes showed autophagy involvement in enhanced cytotoxicity.Conclusions. Thus, autophagy inhibition on different stages of this process could overcome resistance to TMZ and be applicable as potent target in metastatic melanoma treatment.